2021
DOI: 10.1002/stem.3428
|View full text |Cite
|
Sign up to set email alerts
|

DUSP5 Promotes Osteogenic Differentiation Through SCP1/2-Dependent Phosphorylation of SMAD1

Abstract: Dual-specificity phosphatases (DUSPs) are defined by their capability to dephosphorylate both phosphoserine/phosphothreonine (pSer/pThr) and phosphotyrosine (pTyr). DUSP5, a member of DUSPs superfamily, is located in the nucleus and plays crucially regulatory roles in the signaling pathway transduction. In our present study, we discover that DUSP5 significantly promotes osteogenic differentiation of mesenchymal stromal cells (MSCs) by activating SMAD1 signaling pathway. Mechanistically, DUSP5 physically intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Taken together, this evidence suggests that ataluren may act in the targeted management of hBMMSC osteogenic differentiation. Furthermore, the transcriptome sequencing analysis results showed that 50 µM ataluren upregulated DUSP5 most signi cantly, which elevated MSC osteogenic differentiation through the BMP-SMAD pathway, as demonstrated by our group previously (45). It was also suggested that DUSP5 overexpression inhibits NF-κB pathway activation and thereby controls in ammation (46).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Taken together, this evidence suggests that ataluren may act in the targeted management of hBMMSC osteogenic differentiation. Furthermore, the transcriptome sequencing analysis results showed that 50 µM ataluren upregulated DUSP5 most signi cantly, which elevated MSC osteogenic differentiation through the BMP-SMAD pathway, as demonstrated by our group previously (45). It was also suggested that DUSP5 overexpression inhibits NF-κB pathway activation and thereby controls in ammation (46).…”
Section: Discussionmentioning
confidence: 53%
“…3b). DUSP5 has been suggested to enhance MSC osteogenic differentiation through the BMP-SMAD pathway (Liu et al, 2021). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed the most signi cant enrichment in the transforming growth factor beta (TGF-β) signaling pathway (Fig.…”
Section: Ataluren Promotes Hbmmsc Osteogenic Differentiation Through ...mentioning
confidence: 99%
“…aortic valve interstitial cells, periodontal ligament stem cells, and adipose tissue-derived stem cells [25][26][27][28]. Importantly, SMAD1 is involved in OP by promoting the osteogenesis of BSMCs [25,29]. Meanwhile, SMAD1 at phosphorylation can be detected in osteoclasts and has been proven to be vital in osteoclast differentiation and activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…DUSP5 protein plays an important role in the maintenance of pluripotency in mouse embryonic stem cells and may be required for embryoid body development [ 32 ]. DUSP5 promotes osteogenic differentiation through SCP1/2-dependent phosphorylation of SMAD1 [ 33 ]. MPP2 gene encodes palmitoylated membrane protein 2, which is a member of the membrane-associated scaffold protein family known as MAGUKs (membrane-associated guanylate kinase homologs) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding in this study is the mutation p.Ala220Met of the DUSP5 gene in all teratomas. DUSP5 protein plays an important role in the maintenance of stem cell pluripotency [ 32 ] and osteogenic differentiation [ 33 ]. Osteogenic differentiation is another characteristic of teratomas, i.e., bone or tooth formation.…”
Section: Discussionmentioning
confidence: 99%